Characteristics of autoantibodies targeting 14-3-3 proteins and their association with clinical features in newly diagnosed giant cell arteritis. (7th January 2017) - Kistner, Anne; Bigler, Marc B.; Glatz, Kathrin; Egli, Simon B.; Baldin, Fabian S.; Marquardsen, Florian A.; Mehling, Matthias; Rentsch, Katharina M.; Staub, Daniel; Aschwanden, Markus; Recher, Mike; Daikeler, Thomas; et al.
Abstract: Objectives. Autoantibodies are useful biomarkers for diagnosing and monitoring treatment in some autoimmune diseases. Antibodies against isoforms of 14-3-3 protein have been proposed as biomarkers for the presence of aortic aneurysm in large-vessel vasculitis (LVV). Here, we aimed to evaluate the diagnostic role and potential immunopathological involvement of anti–14-3-3 antibodies in newly diagnosed LVV patients. Methods. Antibodies against three isoforms of 14-3-3 (γ, ɛ and ζ) were measured in 90 subjects: 48 GCA and 3 Takayasu's arteritis (TA) patients, and 39 controls (non-inflammatory and inflammatory diseases), using a multiplexed bead-based immunoassay and immunoprecipitation studies. The positive cut-off value was defined based on young healthy controls. Anti–14-3-3 IgG antibodies in LVV patients were compared with those in controls in order to assess their diagnostic performance, and the relationship of anti–14-3-3 IgG antibodies to the immunohistopathology of artery explants was assessed. Results. Antibodies against all three 14-3-3 isoforms were detected in LVV patients as well as in age-matched inflammatory and non-inflammatory controls. Among LVV patients, detection of antibodies targeting 14-3-3 ɛ and ζ was associated with more severe disease. Detection of antibodies against 14-3-3 γ was linked to latent Toxoplasma gondii infection, a parasite that secrets a 14-3-3 homologue, suggesting potential cross-reactivity. Conclusion. Detection of antibodies against 14-3-3 proteins at the time of LVV diagnosis is not disease-specific. Their presence at high levels in LVV patients with stroke, aortitis and—in a previous study—aneurysm formation may indicate an association with extensive tissue destruction. The relevance of 14-3-3 antibodies in non-LVV patients needs to be investigated in larger cohorts.